2019
DOI: 10.1088/1742-6596/1402/5/055009
|View full text |Cite
|
Sign up to set email alerts
|

Studies on degradation of rice husk ash filled in polypropylene composite films under natural weathering condition

Abstract: Natural weathering of rice husk ash filled in polypropylene composite films has been investigated by exposing the samples to a tropical clime for 4 months with max-min temperature 22 - 30°C and relative humidity 75%. In this study, the film composites filled with rice husk ash for decay to get the composites that has good mechanical performance after exposure in natural weathering. Rise husk ash filled in film composite polypropylene effect of filler loading was 1, 2, 3, 4 and 5% and compare with neat composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The glycerol effect on bionanocomposite film can also be indicated by a hydrogen bond competition among polymers and polymer-plasticizers when plasticizers are incorporated into the polymer matrix [22]. Similar results can be observed in other PVA film studies incorporating plasticizers such as sorbitol, propylene glycol, and polyethylene glycol [25][26][27]. Therefore, it can be assumed that PVA-based films will show a more dense and rigid form with increasing levels of CNC and less glycerol incorporation.…”
Section: Tensile Strength Of Filmssupporting
confidence: 61%
“…The glycerol effect on bionanocomposite film can also be indicated by a hydrogen bond competition among polymers and polymer-plasticizers when plasticizers are incorporated into the polymer matrix [22]. Similar results can be observed in other PVA film studies incorporating plasticizers such as sorbitol, propylene glycol, and polyethylene glycol [25][26][27]. Therefore, it can be assumed that PVA-based films will show a more dense and rigid form with increasing levels of CNC and less glycerol incorporation.…”
Section: Tensile Strength Of Filmssupporting
confidence: 61%
“…This study showed that the addition of high glycerol and NCC decreased the thickness, tensile strength, and elongation of the biocomposite film. Aprilia et al also reported that the irregular structure of the reinforcing material reduced composite strength because of the bonds’ inability to support the stress transfer of the polymer matrix [ 51 ]. The weakness in the interfacial areas would decrease the effect of stress transfer from the polymer matrix to the filler component, lowering the strength of the films [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bimodal porosity exhibited by RHA provided enhanced mechanical and thermal properties via capillary effect. Aprilia and co-workers 37,38 reported use of RHA in PP leading to the composites with improved thermal stability.…”
Section: Introductionmentioning
confidence: 99%